Fecal coliform bacteria and factors related to its growth at the Sekotong shallow wells (West Nusa Tenggara, Indonesia) - Sinaga, Doni Marisi; Robson, Mark Gregory; Gasong, Beatrix Trikurnia; Halel, Adonia Getse; Pertiwi, Dian (YCAB Publisher & IAKMI SULTRA, 2016)
Background: The poor sanitation and small numbers of households who own toilet in Sekotong regency may relate to the diarrheal events due to the fecal coliform contamination in drinking water.Aim: This paper aims to provide the concentrations of fecal coliform bacteria in shallow well waters and the factors associated to its growth.Method: Fifteen groundwater samples were collected from 5 shallow wells to provide the concentrations of total fecal coliform bacteria (FC), mercury concentration, inorganic nitrogen compounds (represent as ammonia, nitrate, and nitrite), total phosphorus (TP), dissolved oxygen (D), pH, and salinity. The concentration of the parameters was then compared to the safe limit set by World Health Organization (WHO).Results: The results indicated that the drinking water resources at the Sekotong regency were contaminated by coliform and mercury. One location with low mercury concentration was recorded with E. coli contamination. Residence, agriculture, and animal livestock were subjected as the sources of coliform contamination. Mercury concentrations may inverse the growth of FC. No apparent relationship was found between total phosphorous and inorganic nitrogen compounds to FC growth. However, we recognized the FC growth responded positively to the level of phosphorous in waters, but associated negatively to nitrate concentration. An inverse correlation was also found between coliform survival and salinity in this study. The pH range at 6.05 – 6.50 supported FC survival.Conclusion: The drinking water resources at the Sekotong shallow wells were contaminated by coliform and mercury. It is important for local government to inform drinking water protection and treatment.